Analysis of the application of refined management in engineering construction management based on the Computer Dynamic Network System. Issue 3 (February 2021) - Jiao, Lili
Abstract: At present, China's construction engineering field shows a trend of high output value, low profit input and small output. The main reason for this problem is the serious shortage of construction engineering management, which makes the enterprise have no method to reduce production cost and input. Therefore, the construction and construction industry should apply the fine management in the development, which is of great importance to the production, cost reduction and efficiency enhancement in the actual construction process. Using computer network technology and database technology to construct a computer dynamic network system, based on the system, this paper discusses the application of fine management in the construction process management, and elaborates on the economic management application strategy for cost management and quality management in the project production.